Berberine Potentiates Insulin Secretion and Prevents β-cell Dysfunction Through the miR-204/SIRT1 Signaling Pathway - Lv, Xiaoyan; Zhao, Yali; Yang, Xuehan; Han, Hao; Ge, Yue; Zhang, Meishuang; Zhang, Hansi; Zhang, Ming; Chen, Li (Frontiers in Pharmacology, 2021)
Pancreatic β-cell dysfunction is a key link during the progression of type 2 diabetes (T2DM), and SIRT1 participates in the regulation of various physiological activities of islet β-cells. However, as a key link in signal transduction, it is not clear how SIRT1 is regulated. By TargetScan prediction, we found that miR-204, which is enriched in islets, has highly complementary binding sites with SIRT1. Therefore, we speculate that miR-204 may be the upstream regulatory target of SIRT1 in islets and thus participate in the occurrence of β-cell dysfunction. In this study, we explored the association between miR-204 and β-cell dysfunction, the therapeutic effects of berberine (BBR) on β-cell function and the possible mechanisms. We found that miR-204 increased and SIRT1 mRNA and protein levels decreased significantly in islets both in vivo and in vitro. MIN6 cells induced by palmitic acid exhibited increased apoptosis, and the accumulation of insulin and ATP in the supernatant decreased. Importantly, palmitic acid treatment combined with miR-204 silencing showed opposite changes. MiR-204 overexpression in MIN6 cells increased apoptosis and decreased insulin and ATP production and SIRT1 expression. SIRT1 overexpression reversed the damage to β-cells caused by miR-204. The BBR treatment effectively improved insulin synthesis, reduced miR-204 levels, and increased SIRT1 expression in islet tissue in diabetic mice. Overexpression of miR-204 reversed the protective effect of BBR on apoptosis and insulin secretion in MIN6 cells. Our study identifies a novel correlation between miR-204 and β-cell dysfunction in T2DM and shows that administration of BBR leads to remission of β-cell dysfunction by regulating the miR-204/SIRT1 pathway.